The generalized triple difference of \(χ^{3}\) sequence spaces - Subramanian, N.; Esi, Ayhan (Global Journal of Mathematical Analysis, 2015)
In this paper we define some new sequence spaces and give some topologicalÂ properties of the sequence spaces \(χ^{3}\left( Δ_{v}^{m},s, p\right)\) and \(Λ^{3}\left( Δ_{v}^{m},s, p\right) \) and investigate someÂ inclusion relations.